2020
DOI: 10.3389/fmars.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New Shore-Based Vessel Traffic Monitoring System Within San Francisco Bay

Abstract: Vessel traffic management systems can be employed for environmental management where vessel activity may be of concern. One such location is in San Francisco Bay where a variety of vessel types transit a highly developed urban estuary. We analyzed vessel presence and speed across space and time using vessel data from the Marine Monitor, a vessel tracking system that integrates data from the Automatic Identification System and a marine-radar sensor linked to a high-definition camera. In doing so, we provide dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Fortunately, recent technological advances associated with automatic identification system (AIS), now means that ship-based mobility patterns can be monitored on a global scale [22][23][24] , thereby providing a unique opportunity to monitor the location of large ocean-going ships, passenger liners, and fishing vessels anywhere in the world at high temporal resolution [25][26][27] . Consequently, AIS can provide unparalleled insights into shipping-derived impacts and conservation planning at multiple spatial and temporal scales 4,[27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent technological advances associated with automatic identification system (AIS), now means that ship-based mobility patterns can be monitored on a global scale [22][23][24] , thereby providing a unique opportunity to monitor the location of large ocean-going ships, passenger liners, and fishing vessels anywhere in the world at high temporal resolution [25][26][27] . Consequently, AIS can provide unparalleled insights into shipping-derived impacts and conservation planning at multiple spatial and temporal scales 4,[27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this research was to evaluate the spatial and temporal extent of potential fishing activity in the vicinity of California MPAs using shore-based marine X-band radar, a solution for tracking non-participatory vessels [43,44]. Marine Monitor (M2) systems (https://protectedseas.net/marine-monitor-m2) strategically located onshore near no-take MPAs were used to track vessel activity autonomously and continuously via radar for one year.…”
Section: Introductionmentioning
confidence: 99%
“…Despite historic occupancy, sea otters have not continuously inhabited San Francisco Bay since the mid-19th century, after being extirpated during the Maritime Fur Trade (Ogden, 1941). Today San Francisco Bay is host to three major metropolitan cities, bayfront crude oil refineries, fast passenger ferries (median speed > 55 km/h), and five commercial shipping ports-some of the busiest in the world (Grobar, 2008;Jensen et al, 2015;Cope et al, 2020). There is an ever-present risk of large oil spills, historically proven to be devastating events for all kinds of wildlife (Garrott, Eberhardt & Burn, 1993;Peterson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An examination of deceased otters from the Exxon Valdez oil spill found that exposure to oil through ingestion or inhalation as a result of grooming to try and rid their fur of oil resulted in pathological lesions in the lungs, liver, and kidneys, and provoked a stress response that lead to shock and consequent mortality (Lipscomb et al, 1994). In addition, the Bay is popular for recreational boating and fishing, making the waterways of San Francisco Bay heavily trafficked by vessels of all types (Cope et al, 2020). There are few limits on the speed of vessels traveling within the Bay, apart from a 15 knots (27.8 km/h) speed limit imposed on large commercial shipping vessels while navigating the shipping channels (Harbor Safety Committee, 2009).…”
Section: Introductionmentioning
confidence: 99%